AN ANALYSIS OF FACTORS DETERMINING SELECTION OF STOCKS: AN EMPIRICAL STUDY OF INDIAN RETAIL INVESTORS (Journal of Informatics Education and Research, 2025)
In India, investors in stocks. are influenced by financial metrics, psychological biases, market trends, and socio-economic factors. Grasping these helps to explain investors' conduct in the financial jungle of India, as it matures. Metric. Financial data is a major driver of investment choices. For example, retail investors check out a company's financial strength and future prospects by focusing on such key performance indicators as profitability, growth of revenues, and return to equity. They also commonly use measures such as earnings per share and price/earnings ratios, to judge the level of valuation return. Many retail investors are influenced by the herd, following market trends and doing what other people do. Today there are many young "traders" who will take great risks based on advice of unknown origin and lacking any evidence basis. Stock choice is also influenced by demographic factors. Younger investors tend to have it higher and so often favour growth stocks, whereas older people usually prefer stable dividend-paying companies. Higher income and education levels normally are associated with a stronger tendency to invest in shares as a result of greater access to financial information and resources. A sample of 261 was collected from investors with different income slab. The factors that determining selection of stocks are Financial Factors, Behavioral and Psychological Factors, Market and Economic Factors, and External Influences.